Hubungan Antara Status Gizi, Pola Makan, Aktivitas Fisik dan Stres dengan Gangguan Siklus Menstruasi - Desta Marsahusna Wanggy; Elisa Ulfiana; Suparmi Suparmi (Universitas Ngudi waluyo, 2022)
Teenagers experience menstruation at the age of 12-13 years old. This is a physiological process experienced because this age the reproductive organs mature which have an important role for physical and psychological well. Things that affect menstrual disorders are stress levels, hormonal, high and low BMI, diet, nervous system, changes in vascularization, psychology, chronic disease, physical activity and drug consumption. The purpose of this study was to determine the Relationship between Nutritional Value, Diet, Physical Activities, and Stress with Menstrual Cycle Disorders toward Teenagers at SMA N 1 Parakan. This research was conducted in the Parakan. This type of research is an analytic study using a cross-sectional. The research population is young women in SMA N 1 Parakan. The sampling technique is by using random sampling technique. The research sample was 67 respondents using the formula for sampling size. The results showed that most of the respondents had normal Nutritional Value as many 21 respondents (31.3%), moderate eating patterns as many 29 (43.3%), light physical activity levels as many 29 (43.3%), moderate stress levels as many 22 respondents (32.8%) and regular menstrual cycles as many 47 (70.1%). The results of the chi-square test showed a relationship between nutritional value and the menstrual cycle with a p-value of 0.036<0.05, there was a relationship between diet and the menstrual cycle with a p-value of 0.047<0.05, there was a relationship between the level of physical activity and menstrual cycle with a p-value of 0.044<0.05, and the relationship between stress levels and the menstrual cycle with a p-value of 0.035<0.05. The results of this study are expected that young women pay more attention to the menstrual cycle and pay attention to things that can affect the menstrual cycle.Â Abstrak Remaja mengalami menstruasi pada usia 12-13 tahun. Hal ini adalah proses fisiologis yang dialami karena pada usia ini terjadi kematangan organ reproduksi yang memiliki sebuah peranan penting untuk kesejahteraan fisik maupun psikologis. Hal yang mempengaruhi gangguan menstruasi yaitu tingkat stres, kadar hormonal, tinggi rendahnya IMT, pola makan, sistem syaraf, perubahan vaskularisasi, psikologi, penyakit kronis, aktivitas fisik dan konsumsi obat. Tujuan dalam penelitian ini yaitu mengetahu hubungan antara status gizi, pola makan, aktivitas fisik dan stress dengan gangguang siklus menstruasi pada remaja putri di SMA N 1 Parakan.Penelitian ini dilakukan di wilayah Parakan. Jenis penelitian ini merupakan penelitian analitik dengan menggunakan desain cross-sectional. Populasi penelitian adalah remaja putri di SMA N 1 Parakan. Teknik pengambilan sampel yaitu dengan menggunakan tehnik random sampling. Sampel penelitian 67 responden dengan menggunakan rumus besaran sampling. Hasil penelitian menunjukkan sebagian besar responden memiliki status gizi normal sebanyak 21 responden (31,3%), pola makan cukup sebanyak 29 (43,3%), tingkat aktivitas fisik ringan sebanyak 29 (43,3%), tingkat stres sedang sebanyak 22 responden (32,8%) dan siklus menstruasi teratur sebanyak 47 (70,1%). Hasil uji chi-square didapatkan hubungan antara status gizi dengan siklus menstruasi dengan p-value sebesar 0,036<0,05, ada hubungan antara pola makan dengan siklus menstruasi dengan p-value sebesar 0,047<0,05, ada hubungan antara tingkat aktivitas fisik dengan siklus menstruasi dengan p-value sebesar 0,044<0,05, dan hubungan antara tingkat stres dengan siklus menstruasi dengan p-value sebesar 0,035<0,05. Hasil penelitian ini diharapakan agar remaja putri lebih memperhatikan siklus menstruasi dan memperhatikan hal yang dapat mempengaruhi siklus menstruasi.